Instrument Development of a Risk Barometer to Measure Extremism Behavior Among Early Youth in Malaysia - D’Silva, Jeffrey Lawrence (Animo Repository, 2019)
Undoubtedly, extremism is a current concern that has a negative impact on peace and sustainable society. Not much effort is made to identify the critical factors that contribute to individuals to become violent extremists. The aim of the study is to develop a valid and reliable instrument, the Risk Barometer to Measure Extremism Behaviour (RBMEB), to measure extremist behavior among early youth. The data collection process involved two phases comprising more than 800 early youth studying in schools and institutions of higher learning in Klang Valley, Malaysia. At the initial stage, the instrument had 19 domains with 151 items. Exploratory factor analysis was carried out, and this process reduced the RBMEB to 14 domains with 106 items. The Cronbach’s alpha on all 14 factors was between .650 and .912, indicating the soundness of the instrument. The RBMEB is believed to be the only validated and reliable instrument that indicates the risk barometer to measure extremism among early youth. Future research could apply this instrument as the basis for the construct of extremism, and it could be used to make comparisons with socio-demographic factors as well as identifying predictive factors of extremist behavior.